(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Risk assessment in capital allocation in the management of the process of capital and financial provision, risk assessment in capital allocation plays a decisive role and ensures their use. Effective financing involves planning, forecasting and monitoring cash flows to maintain liquidity and meet financial obligations.